Phi production as a measure of the strangeness content of the nucleon - Henley, E. M.; Krein, G.; Williams, A. G. (Elsevier, 1992)
We propose studies of lepto- and photo-production of phi mesons as a probe of the ss content of the nucleon. We calculate and compare contributions to the ep→epφ cross-section from ss-knockout and from diffractive production through vector meson dominance. The OZI rule and the ideal mixing of the phi are expected to suppress competing production mechanisms. We find that the knockout and diffractive contributions are of similar size when we assume an admixture of ≅(10-20)% strange quarks in the nucleon. The model dependence of the knockout prediction is examined. We argue that it should be possible to distinguish these two contributions through their angular behavior and through polarization experiments. © 1992.